Assessment and Management of Radioactive and Electronic Wastes - El-Din Saleh, Hosam (IntechOpen, 2020)
Hazardous waste has been defined as waste that is either in a solid, liquid, or gas form, which contributes significantly to serious irreversible or incapacitating reversible illnesses and poses a potential hazard to human health or the environment, depending on its quantity, concentration, and physical, chemical, or infectious characteristics. Hazardous waste risk assessment is a quantitative means of assessing the potential adverse effects of exposure on human health.Management of hazardous waste is a very important process for saving the environment and human life. Traditional and innovative techniques for the treatment and solidification of hazardous waste make for interesting research and study. Proper storage of hazardous waste ensures proper segregation of waste, separation of incompatible wastes, easy access to wastes, reasonable protection against vandalism, and adequate secondary containment. Hazardous wastes are generally stored in different modified containers, including drums and tanks. Prevention or minimization of hazardous waste and improving control methods are introduced as risk management options.Many countries, including developing countries, have taken steps in the right direction to minimize and manage hazardous waste, not only by cleaning up contaminated sites, but also by controlling and reducing the generation of hazardous wastes.